Allergen - Shamsadin Athari, Seyyed (IntechOpen, 2017)
Allergy is a main problem of public health in the world. Many people in all countries are suffering from this problem. Some diseases (i.e. allergic rhinitis, allergic asthma, food allergy, urticaria, eczema, etc.) have allergic reaction pathophysiology, and with control of allergic mechanisms, these diseases can be controlled and cured. The current book entitled Allergen has focused on allergy, mechanism, diagnosis, treatment, and other related problems. Chapters of the book have good data on allergy-based medical sciences and would be a benefit for all researchers in immunology, allergy, and asthma fields. Current discussions would be useful for prevention, diagnosis, treatment, and follow-up of atopic patients. We hope these chapters could be a new approach in immunotherapy of allergic diseases and help in the progress of healthy system.